2020
DOI: 10.21203/rs.3.rs-58887/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploration the mechanism of doxorubicin-induced Heart failure in Rats by integration of proteomics and metabolomics data

Abstract: Background Heart failure is currently a worldwide systemic disease with high morbidity and mortality and is very common. At present, many studies have shown that heart failure is associated with obesity, hypertension and diabetes, but it is still unable to prevent the disease from progressing. Here, we elucidate the molecular mechanisms of doxorubicin–induced harmful effects on rat cardiac metabolism and function from a new perspective, using metabonomics and Proteomics analysis data. Methods The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…With the advent of techniques, comprehensive omics strategies come into vision and multi-omics analysis has been applied in DOX-associated cardiotoxicity for high-throughput data of every single cell, providing beneficial for diagnosis and therapy [105][106][107]. RNA-sequencing analysis (RNA-seq) and proteomics analysis were performed in hearts detecting thousands of genes or proteins and distinguished significantly differential expression groups (DEGs) [108][109][110][111].…”
Section: Multi-omics Reflecting a Whole Picture Of Mechanisms Behind Dox-induced Cardiotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of techniques, comprehensive omics strategies come into vision and multi-omics analysis has been applied in DOX-associated cardiotoxicity for high-throughput data of every single cell, providing beneficial for diagnosis and therapy [105][106][107]. RNA-sequencing analysis (RNA-seq) and proteomics analysis were performed in hearts detecting thousands of genes or proteins and distinguished significantly differential expression groups (DEGs) [108][109][110][111].…”
Section: Multi-omics Reflecting a Whole Picture Of Mechanisms Behind Dox-induced Cardiotoxicitymentioning
confidence: 99%
“…Subsequent bioinformatics analysis given the fact the altered peptides were closely associated with mitochondrial function, energy generation, oxidationreduction process and oxidative phosphorylation [113]. Bioinformatics profiling of integrated multi-omics screened common pathways involved in DOX-induced cardiotoxicity, which is indicated to be associated with energy metabolism, amino acid metabolism, fatty acid metabolism, and enzyme activities [106,107]. However, the differences in experimental models, grouping methods, analysing approaches, and screening conditions lead to various database.…”
Section: Multi-omics Reflecting a Whole Picture Of Mechanisms Behind Dox-induced Cardiotoxicitymentioning
confidence: 99%
“…These decreases were thought to be due to tyrosol's antioxidant effect on heart tissue, which inhibits lipid peroxidation. Doxorubicin administration causes various histopathological changes, such as cardiomyocyte vacuolization in heart tissue, increased extracellular fibrosis, muscle fiber disorder, myofibril loss, enlarged and abnormally shaped mitochondria, inflammatory cell infiltration, increased cell death, cardiomyocyte apoptosis, edema of myocardial cells, myocardial tissue hemorrhage, blood vessel occlusion, pycnotic nuclei and necrosis (Kumrala et al 2015, Haybara et al 2019, Ma et al 2019, Öner et al 2019, Liao et al 2020, Sandamali et al 2020, Tiana et al 2020, Yuan et al 2020, Ahmed et al 2021, Wan et al 2021. When the heart tissue samples from the control and tyrosol groups were examined, the cardiac muscle cells were found to have normal histological features.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, this study found evidence of reduced beta-oxidation of fatty acids and enhanced oxidative stress with lower levels of superoxide dismutase in the myocardial tissue. Based on these, they suggested that the reduced energy production and reactive oxygen species accumulation led to dysfunctional myocardial contractility and HF [21].…”
Section: Rat Model Studiesmentioning
confidence: 99%